2010
DOI: 10.1155/2010/426973
|View full text |Cite
|
Sign up to set email alerts
|

Clear-Cell Adenocarcinoma of Vesical Origin: A Case Study of Metastatic Disease Treated with Chemotherapy

Abstract: Vesical clear cell adenocarcinoma is an uncommon tumour. The description of nearly all published cases focuses on histological issues, providing few clinical particulars and limited followup. The treatment choice is resection. No publications have been found regarding systemic treatments for advanced disease. We present a case of metastatic clear cell adenocarcinoma of the bladder treated with chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Alvarez et al [ 29 ] concluded the following. The combination of clear cell and transitional adenocarcinoma in this case did not allow for the role of each histology in determining the outcome and the poor response to therapy.…”
Section: Discussion and Miscellaneous Narrations From Reported Casmentioning
confidence: 99%
See 2 more Smart Citations
“…Alvarez et al [ 29 ] concluded the following. The combination of clear cell and transitional adenocarcinoma in this case did not allow for the role of each histology in determining the outcome and the poor response to therapy.…”
Section: Discussion and Miscellaneous Narrations From Reported Casmentioning
confidence: 99%
“…Alvarez et al [ 29 ] reported a 49-year-old woman who underwent transurethral resection of bladder tumour on two occasions. The final histological diagnosis of the tumour was clear cell adenocarcinoma with infiltration into the muscle layer of the bladder (pT2).…”
Section: Discussion and Miscellaneous Narrations From Reported Casmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that chemotherapy for more advanced disease provides no survival benefit. Agents used in the past have included cisplatin, doxorubicin, cyclophosphamide, and 5-Fluoruracil [12,13]. These have only been used in sporadic cases and so it is uncertain whether there are any untried chemotherapy agents which may provide some benefit.…”
Section: Discussionmentioning
confidence: 99%